Peran POKMASWAS dalam Menjaga Habitat Penyu di Pulau Pinang, Kecamatan Tambelan, Kabupaten Bintan - Fera Mardiani; Nur Asri; Siti Arieta (Pusat Riset dan Inovasi Nasional, 2025)
The role of Pokmaswas in protecting turtle habitats on Pinang Island, Tambelan District, Bintan Regency, is the subject of this study. Indonesia has many marine species, one of which is the turtle habitat. In Indonesia, turtle habitats must be protected in accordance with applicable regulations. There is a sea turtle habitat that must be protected, located in Pulau Pinang Village in Tambelan District, Bintan Regency, which is an area rich in natural resources, including the presence of sea turtle habitats that are one of its ecological attractions. This research was conducted using a qualitative approach involving observation and interviews. The research shows that Pokmaswas ensures the preservation of sea turtle habitats through conservation, education, and monitoring. The success of Pokmaswas is influenced by public awareness, government support, and collaboration among stakeholders. To preserve the sea turtle habitat on Pulau Pinang, this study recommends increasing conservation efforts and public awareness. Community Monitoring Groups (Pokmaswas). plays an important role in protecting turtle habitats on Pinang Island, Tambelan District, Bintan Regency. Through monitoring, which plays a role in protecting turtle habitats on Pinang Island, it is very important in preserving the sea and marine habitats, including turtle habitats that are threatened with extinction. Endangered species face various threats from both natural factors and human intervention. Pokmaswas plays an active role in monitoring and conservation by involving local communities in turtle egg and habitat protection activities. Through environmental education and awareness programs, communities are encouraged to participate in efforts to mitigate threats, such as hunting and habitat destruction.